Verifiable three-party secure key exchange protocol based on eigenvalue - Yanshuo ZHANG; Zehao WANG; Zhiqiang WANG; Huiyan CHEN (Tongxin xuebao)
In order to solve the problem that the traditional key exchange protocol,which was not flexible enough and flawed in security,cannot provide the function of three-party key negotiation,firstly,a simple and flexible three-party key exchange scheme that can resist man-in-the-middle attacks was proposed with the help of secret matrix eigenvalues.However,the validity of key exchange cannot be verified by the scheme,and counterfeiting by middlemen can’t be prevented.Then based on it,the secret matrix was reconstructed,where the matrix order was a large even number,and all the eigenvalues appeared in pairs,similar to the diagonal matrix.Based on the special secret matrix,the verification part which can be used to verify the legitimacy of the communication party was introduced to the scheme,and the verifiable three-party key exchange protocol based on the eigenvalue was given.The protocol not only solved the problem of three-party key exchange,but also verified identity legitimacy.It is proved that it’s feasible to design a three-party key exchange protocol by the eigenvalue.The final protocol is both secure and efficient.